Oncolytic viruses in head and neck cancers: clinical applications and therapeutic potential - Gupta, Aditi; Chavan, Samiran Ranjit; Gadepalli, Ravisekhar; Pareek, Puneet (Frontiers in Microbiology, 2025)
BackgroundHead and neck squamous cell carcinoma remains a significant global health burden, particularly in low-resource regions like India. Conventional treatments often fall short in achieving durable responses, prompting the need for novel therapies.ObjectiveThis review outlines the clinical progress, mechanism of action, and emerging therapeutic potential of oncolytic viruses (OVs) in the management of HNSCC, with an emphasis on ongoing trials, approved agents, and future directions.MethodsData were extracted from published literature on PubMed and ClinicalTrials.gov. Focus was placed on mechanisms of viral action, regulatory approvals, trial outcomes, and rational combinations with existing therapies.FindingsOncolytic viruses exert dual antitumor effects through selective viral replication and immune system activation. Talimogene laherparepvec (T-VEC) remains the only FDA-approved OV, while others like Oncorine and Teserpaturev show regional efficacy. Multiple early-phase trials are underway evaluating OV combinations with checkpoint inhibitors, chemotherapy, and radiotherapy. Although clinical responses have been encouraging, challenges such as tumor penetration, immune clearance, and hypoxic environments remain.ConclusionOncolytic virotherapy holds considerable promise in HNSCC. Advances in virus design, delivery platforms, and personalized approaches are essential for transitioning this modality from experimental settings into routine clinical practice.